Réponses

2013-12-20T22:05:20+01:00
Bonsoir

A=29 sur 3 + moins 22 sur 3

A=\dfrac{29}{3}+\dfrac{-22}{3}\\\\A=\dfrac{29}{3}-\dfrac{22}{3}\\\\A=\dfrac{7}{3}

B=20 sur 12 moins 5 sur 15

B=\dfrac{20}{12}+\dfrac{5}{15}\\\\B=\dfrac{4\times5}{4\times3}+\dfrac{5\times1}{5\times3}\\\\B=\dfrac{5}{3}+\dfrac{1}{3}\\\\B=\dfrac{6}{3}\\\\B=2

C=moins 5sur 3 moins ( 6sur4 fois 8 sur 18) + 3 sur 2

C=\dfrac{-5}{3}-(\dfrac{6}{4}\times\dfrac{8}{18})+\dfrac{3}{2}\\\\C=\dfrac{-5}{3}-(\dfrac{1}{4}\times\dfrac{8}{3})+\dfrac{3}{2}\\\\C=\dfrac{-5}{3}-(\dfrac{1}{1}\times\dfrac{2}{3})+\dfrac{3}{2}\\\\C=\dfrac{-5}{3}-\dfrac{2}{3}+\dfrac{3}{2}\\\\C=\dfrac{-7}{3}+\dfrac{3}{2}\\\\C=\dfrac{-14}{6}+\dfrac{9}{6}\\\\C=\dfrac{-5}{6}